Reevaluation of the South Asian MYBPC3Δ25bp Intronic Deletion in Hypertrophic Cardiomyopathy. (June 2020) - Harper, Andrew R.; Bowman, Michael; Hayesmoore, Jesse B.G.; Sage, Helen; Salatino, Silvia; Blair, Edward; Campbell, Carolyn; Currie, Bethany; Goel, Anuj; McGuire, Karen; Ormondroyd, Elizabeth; Sergeant, Kate; et al.
Abstract : Background: The common intronic deletion, MYBPC3 Δ25, detected in 4% to 8% of South Asian populations, is reported to be associated with cardiomyopathy, with ≈7-fold increased risk of disease in variant carriers. Here, we examine the contribution of MYBPC3 Δ25 to hypertrophic cardiomyopathy (HCM) in a large patient cohort. Methods: Sequence data from 2 HCM cohorts (n=5393) was analyzed to determine MYBPC3 Δ25 frequency and co-occurrence of pathogenic variants in HCM genes. Case-control and haplotype analyses were performed to compare variant frequencies and assess disease association. Analyses were also undertaken to investigate the pathogenicity of a candidate variant MYBPC3 c.1224-52G>A. Results: Our data suggest that the risk of HCM, previously attributed to MYBPC3 Δ25, can be explained by enrichment of a derived haplotype, MYBPC3 Δ25/ −52, whereby a small subset of individuals bear both MYBPC3 Δ25 and a rare pathogenic variant, MYBPC3 c.1224-52G>A. The intronic MYBPC3 c.1224-52G>A variant, which is not routinely evaluated by gene panel or exome sequencing, was detected in ≈1% of our HCM cohort. Conclusions: The MYBPC3 c.1224-52G>A variant explains the disease risk previously associated with MYBPC3 Δ25 in the South Asian population and is one of the most frequent pathogenic variants in HCM in all populations; genotyping services should ensure coverage of this deep intronic mutation. Individuals carrying MYBPC3 Δ25 alone are not at increased risk of HCM, and this variant should not be tested in isolation; this is important for the large majority of the 100 million individuals of South Asian ancestry who carry MYBPC3 Δ25 and would previously have been declared at increased risk of HCM. Abstract : Supplemental Digital Content is available in the text.